Pengaruh Strategi Promosi Melalui Media Sosial, Kualitas Pelayanan, dan Word of Mouth Terhadap Loyalitas Pelanggan pada Warung Kopi Cak Kebo: (The Effect of Promotion Strategy Through Social Media, Quality of Service, and Word of Mouth on Customer Loyalty in Cak KeboCoffee Store) - Mochtar Luthfi Effendy; Maheni Ika Sari; Haris Hermawan (UPT Penerbitan Universitas Jember, 2021)
The formulation of the problem in this study is how the Promotion Strategy through Social Media, Service Quality, and Word Of Mouth affect Customer Loyalty. The research objective was to determine and analyze Promotion Strategies through Social Media, Service Quality, and Word Of Mouth partially influence Customer Loyalty. The theory used in this research is marketing management theory, Promotion Strategy through Social Media, Service Quality, Word Of Mouth, and Customer Loyalty. The research was conducted on customers of Cak Kebo Jember Coffee Shop. This type of descriptive quantitative research using purposive sampling method with a sample of 100 respondents. The nature of the research is explanatory. The test tool used is multiple linear regression, with SPSS software version 25.00. Results of Service Quality, and Word Of Mouth have positive values and significance values that meet the testing criteria. Meanwhile, the Promotion Strategy through Social Media has a negative value. This also shows that Service Quality, and Word Of Mouth affect Customer Loyalty and Promotion Strategies through Social Media do not affect Customer Loyalty which means better Service Quality, and Word Of Mouth will have an impact on better Customer Loyalty.